PERAN BINA TAQWA DALAM MEMBANGUN KARAKTER ISLAMI DI MASYARAKAT: SEBUAH PENDEKATAN PENGABDIAN - Nurhidayati, Sri Wahyu; Anggraini, Oci; Setiani, Desi Fitri; Saputra, Cholis Moja; Harmanda, Hary Zainal; Juni Astuti, Dina Putri (CV. Kalimasada Group, 2024)
Community Service (KKN) is one of the pillars of the Tri Dharma of Higher Education in the aspect of community service. This study examines the role of Bina Taqwa in building Islamic character in society through a community service approach from UINFAS Bengkulu KKN Batch III students in providing religious guidance programs for the people of Sido Luhur Village, Seluma Regency. The problems faced by the community service partners include the lack of community understanding of women's fiqh and tajwid in reading the Qur'an. This community service activity was carried out at the Miftahul Jannah ta’lim assembly in hamlet 1-2 related to strengthening and mentoring fiqh of worship. This study uses a qualitative research method using a literature study type of research. The results of the research from this program are effective in increasing community understanding, especially housewives, of women's fiqh and tajwid of the Qur'an. The participatory approach used in this program succeeded in creating a conducive learning atmosphere and motivating participants to study religious teachings more deeply.